Aplikasi Cycocel dalam Pengendalian Getah Kuning Buah Manggis (Garcinia mangostana L.) pada Lahan Kering - Irianto Irianto; Budiyati Ichwan; Mapegau Mapegau (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2013)
The aim of this experiment was to gain the accurate concentration of cycocel growth for controlling of yellow latex mangoesteen in different age level on field water stress. This experiment was conducted in Koto Patah village, Keliling Danau, Kerinci, Jambi and was done from June until November 2011 at the altitude of 800 - 900 meter above sea level. Factorial experiment was arranged in a randomized block design. The first factor was cycocel concentrations: 0; 1.500; 3.000; 4.500; dan 6.000 mg L-1. The second factor was levels of age plants: <30; 30-50; and >50 years. The data were analyzed by using analysis of variance and continued with BNT test at α=5%. The results of experiment showed that: (1) the impact of cycocel on number and weight of perfect fruits depended on the age of manggoesteen; (2) manggoesteens which were less than 30 years old and treated with 4.500 mgL-1 cycocel could increase number and weight of perfect fruits; (3) manggoesteens which were older, 30-50 years old and above 50 years old needed less cycocel namely 1.500 mgL-1 for increasing number and weight of perfect fruis.